Relationship between immune response to pneumococcal conjugate vaccines in infants and indirect protection after vaccine implementation - Ron Dagan (Expert Review of Vaccines, 2019)
Introduction: Streptococcus pneumoniae is a leading cause of morbidity and mortality worldwide. Widespread infant vaccination with pneumococcal conjugate vaccines (PCVs) substantially reduced vaccine-serotype pneumococcal disease by direct protection of immunized children and indirect protection of the community via decreased nasopharyngeal carriage and transmission. Essential to grasping the public health implications of pediatric PCV immunization is an understanding of how PCV formulations impact carriage. Areas covered: Using clinical evidence, this review examines how the immune response to PCVs is associated with subsequent nasopharyngeal carriage reduction in vaccinated infants and toddlers. By combining direct and indirect protection, carriage reduction results in a reduced spread of vaccine serotypes, and eventually, a decrease in vaccine serotype disease incidence in community members of all ages. Expert opinion: The current review presents some of the aspects that influence the overall impact of PCVs on vaccine-serotype carriage, and thus, spread. The link between reduction of vaccine-serotype carriage and the eventual reduction of vaccine-serotype disease in the wider community is described by comparing data from current PCVs, specifically with respect to their ability to reduce carriage of some cross-reacting serotypes (i.e. 6A versus 6B and 19A versus 19F).